Peran Dewan Pengawas Syariah dalam Menjamin Kualitas Produk pada Bank Syariah Indonesia (BSI) - Alvera Zahvania Putri; Defa Irfantara Pramudya; Binti Nur Asiyah (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2025)
Islamic banking in Indonesia, led by Bank Syariah Indonesia (BSI), is experiencing rapid growth, but still faces challenges in product quality and compliance with sharia principles. This article discusses the important role of the Sharia Supervisory Board (DPS) in ensuring that banking products comply with sharia principles, including the supervision of the application of fatwas to ensure that products are free from maysir, gharar, and riba. Through qualitative research based on literature study, DPS is proven to have a strategic role in product and service supervision. However, obstacles such as limited independence and lack of product innovation are the main challenges that need to be overcome. Strengthening the role of DPS and providing adequate regulatory support are important steps to improve the quality of BSI products and services. With these efforts, BSIs are expected to be able to maintain sharia principles as the core of operations, while increasing public confidence in the Islamic banking industry. It also has the potential to support the sustainable growth of the Islamic banking sector in Indonesia, making it more competitive and relevant to the needs of the modern market.